Pengaruh Viral Marketing Dan User-Generated Content (UGC) Terhadap Purchase Decision Produk Skincare Pada Gen Z Melalui Brand Awareness Sebagai Variabel Mediasi - Putri, Salsabila Najichavida; Komaryatin, Nurul (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the influence of viral marketing and user-generated content (UGC) on the purchase decisions of skincare products among Generation Z, with brand awareness as a mediating variable. Generation Z was chosen as the focus of the study because of their active involvement in social media and their strong influence in the beauty market. Their purchasing behavior is often shaped by digital interactions, making them a relevant target group to understand how marketing strategies affect decision-making.Methods: A quantitative approach was applied using a survey method. The sample consisted of 123 respondents from Generation Z who are active skincare product users. Data collection was conducted through a structured questionnaire designed to measure viral marketing, UGC, brand awareness, and purchase decisions. The data were then analyzed using Structural Equation Modeling (SEM) with Smart PLS 4 software. The analysis included testing the measurement model for validity and reliability as well as evaluating the structural model to test hypotheses and mediation effects.Results: The findings indicate that both viral marketing and UGC have significant positive effects on brand awareness and purchase decisions. Additionally, the results confirm that brand awareness significantly mediates the relationship between viral marketing, UGC, and purchase decisions. These results suggest that the visibility and recognition of a brand play a crucial role in strengthening the impact of digital marketing strategies. Overall, the study emphasizes the importance of content-driven campaigns and strong brand positioning in influencing the skincare purchase decisions of Generation Z consumers. Keywords: Viral Marketing, User Generated Content, Brand Awareness, Purchase Decision, Gen Z.